Austempered Ductile Iron with Dual Microstructures: Effect of Initial Microstructure on the Austenitizing Process - Guesser W.L.* (2020)
© 2020, American Foundry Society.This work compares alternatives for the production of high ductility ADI, austempered from an intercritical austenitizing temperature range, with a microstructure of ferrite + ausferrite. Different initial microstructures were selected, including ferrite, pearlite, pearlite + ferrite, martensite and ausferrite. The samples were austenitized within the intercritical zone (795 °C) for different times (up to 12 h) and then austempered at 350 °C. The evolution of the formation and distribution of ferrite and austenite during the austenitizing process for the different initial microstructures was studied. For the selected austenitizing temperature, all of the initial microstructures produced 30% ferrite (70% ausferrite) in the final microstructure (after 12 h). The mechanical properties depend upon the distribution and refinement of the ferrite and ausferrite areas. Spheroidized carbides from pearlite are not completely dissolved during intercritical austenitizing for 2 h. Graphite nodules are an important source of carbon for the austenite formed from starting microstructures of ferrite, pearlite + ferrite and pearlite with grain boundaries being the main pathway for carbon diffusion. Austenitizing started away from the graphite nodules at eutectic cell boundaries due to Si segregation. For starting microstructures of ferrite, pearlite and pearlite + ferrite, a homogeneous distribution of austenite does not occur. Rather, it is concentrated on eutectic cell boundaries and ferrite grain boundaries with large areas of ferrite around the graphite nodules. For starting microstructures of martensite and ausferrite, carbon is evenly distributed and quickly dissolved, resulting in a homogeneous distribution of austenite and ferrite with the best combination of strength and ductility.